(untitled) (Revista Brasileira Multidisciplinar, 2023)
The Primary Health Care (PHC) is the gateway to the brazilian health system. The essential attribute of longitudinality is considered a unique feature of this care model. This article aims to evaluate the essential attribute of longitudinality, through published evidence, from the perspective of Brazilian PHC users. This is an integrative literature review. Data collection was carried out in the Latin American and Caribbean Health Sciences Literature, Nursing Database, MEDLINE and COLECIONA-SUS databases via the Virtual Health Library, using the time frame of five years (2016-2021). A total of seven articles published between 2016 and 2020 that addressed the evaluation of the longitudinality attribute by users were included in the sample. The longitudinality attribute had a low evaluation in the studies, being considered high only in a small portion of the seven articles analyzed, reflecting the need for changes in Brazilian Primary Care.